Achieving Authentic Happiness According to Positive Psychology Martin Seligman and Wahdat al-Syuhud Muhammad Nafis al-Banjari - Jamal, Muhammad Taufiq (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This study examines how to achieve authentic happiness according to the positive psychology of Martin Seligman from a psychological perspective and the concept of wahdat al-syuhud in the book al-Durr al-Nafis by Syekh Muhammad Nafis al-Banjari from the point of view of Sufism. This study tries to explain the journey to achieve authentic happiness from the point of view of positive psychology and Sufism. Which is Martin Seligman with positive psychology as a representation of psychology and Sheikh Muhammad Nafis al-Banjari with Kitab al-Durr al-Nafis as a scientific representation of Sufism. This study uses a qualitative descriptive approach, which is based on library research. This study examines the meaning of authentic happiness, ways to achieve authentic happiness, similarities, similarities, meeting points and separation points of the theories of the two figures. This study examines two scientific perspectives, namely from the point of view of psychology and tasawuf or psycho-sufism. . It can be concluded that there are many ways to achieve happiness, but happiness must be sought through positive ways, because happiness is a positive value.